Architecture, Anarchism, and Human Rights - Bristol, Graeme (MAJ - Malaysia Architectural Journal, 2025)
Architecture is a political act. However, in practice we steadfastly avoid that fact. There is a steep price to pay for that avoidance. If we are to evolve as a profession in the realm of today’s environmental tipping points and socio-economic shifts, we must better understand our place in the development of policy and certainly begin to unpack some of the assumptions governing our decisions about the built environment. The nature of politics concerns the way we choose (or are told) to live together. This relates directly to our assumptions about the design of the built environment. Architecture, though, can and should be asking how we could live together. Robert Kennedy, when running for President in 1968, said: "Some people see things as they are and say, 'why?' I dream things that never were and say, 'why not?' "This tends more towards utopian thinking, and, I believe, it is a natural perspective for architecture. Such a question, though, requires us to discard many of the assumptions made when we start sketching the future and asking ourselves ‘why not?’. In this paper I want to address that question through the lens of a few notable outliers in the field of architecture and the environment: John F.C. Turne and Colin Ward. What would/could architecture be if we challenge our assumptions as we imagine our next steps, as we ask, ‘why not?’